Conflict in Syria, a sign of the judgment day - Siti Sarah, Mohamad Rajimi (2017)
Pusat Islam dan Pembangunan Insan (PIMPIN), together with UMP Library has successfully organized ‘Anda Tanya Ustaz Jawab’ Program recently. The talk with the title ‘Syria Bergolak Tanda Hari Kiamat’ were presented by Amirul Asraf Mat Arif, Head of Promotional & Marketing for Malaysia Life Line for Syria (MLLFS).